Do the disruptive business models of energy companies Solarcity, RWE and d.light fit into theoretical disruption models? - Gallego, Maria Belen Filgueira (2016)
This thesis analyses the case studies of disruptive energy companies SolarCity, RWE and d.light to identify whether each of them fit into one of the academic disruption models: ● Disruption from below. This theory maintains that disruption is when substandard or ‘inferior’ technology ● Disruption from above. This theory starts with a superior product or service which is much more capable than the existing mainstream technology provided ● Big Bang disruption, when products or services have both better performance and lower price and more customization than existing mainstream markets Analysing the SolarCity case study, it seems to fit well in a ‘Big Bang disruption’ model as it clearly changed the rules from day one by making available a completely different service from what the customers of utilities were used to. RWE suffered fits into the ‘disruption from above’ model because clean energy was providing an added value that fossil fuels could not. RWE is now looking to become the disruptor themselves. Analysing the d.light case, it appears in terms of technology the disruption fits in with the ‘disruption from below’ model. d.light works because it is very specific to the particular customer base that they serves and it would be unlike to succeed if the context was different or there was an alternative.